Baleen whale cortisol levels reveal a physiological response to 20th century whaling - Stephen J. Trumble (Nature Portfolio, 2018)
It has recently been found that stress hormones accumulate in the earwax of whales. Here, the authors use these signatures of stress along with time series of ocean warming and whaling pressure to demonstrate that both stressors were correlated with baleen whale stress over several decades.